2014
DOI: 10.3389/fncel.2014.00337
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid potentiates curcumin-mediated neuroprotection in lipopolysaccharide induced rats

Abstract: The etiology of neuroinflammation is complex and comprises multifactorial, involving both genetic and environmental factors during which diverse genetic and epigenetic modulations are implicated. Curcumin (Cur) and valproic acid (VPA), histone deacetylase 1 inhibitor, have neuroprotective effects. The present study was designed with an aim to investigate the ability of co-treatment of both compounds (Cur or VPA, 200 mg/kg) for 4 weeks to augment neuroprotection and enhance brain recovery from intra-peritoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 55 publications
2
13
1
Order By: Relevance
“…These differences may be a result of the different research systems used: The previous study examined a virus system, while the present study investigated SH-SY5Y cells. consistent with our present research, a number of other studies have also confirmed that curcumin exerts biological activities via activation of APE1 (43,44). Subsequently, it was revealed that the knockdown of APE1 by transfection with APE1 siRNA reversed the curcumin-induced protective effects against OGd/R injury in SH-SY5Y cells, suggesting the contribution of APE1 to the neuroprotective effects of curcumin.…”
Section: Discussionsupporting
confidence: 92%
“…These differences may be a result of the different research systems used: The previous study examined a virus system, while the present study investigated SH-SY5Y cells. consistent with our present research, a number of other studies have also confirmed that curcumin exerts biological activities via activation of APE1 (43,44). Subsequently, it was revealed that the knockdown of APE1 by transfection with APE1 siRNA reversed the curcumin-induced protective effects against OGd/R injury in SH-SY5Y cells, suggesting the contribution of APE1 to the neuroprotective effects of curcumin.…”
Section: Discussionsupporting
confidence: 92%
“…The anti‐inflammatory properties of Cur might result from inhibition of proinflammatory cytokines and COX‐2 involved in NF‐κB pathway. In line with our finding, Cur has been found to block the LPS‐mediated induction of COX 2 through inhibition of NF‐κB pathway (Kang et al, , Zaky et al, ). The biological effects of Cur are mainly derived from its ability to either bind directly to various proteins such as COX‐2 or its ability to modulate the intracellular redox state (Hong et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, curcumin is able to suppress IL-6 production in astrocytes located in CNS and downregulate proinflammatory mediators mRNA such as Monocyte Chemoattractant Protein-1 (MCP-1) [42]. Based on a study by Zaky et al, a combination of curcumin with valproic acid could synergistically potentiate neuroprotection effects in neuroinflammatory condition induced lipopolysaccharide in rat and improve recovery [43]. Additionally, curcumin can suppress the TNF-α, IL-6 and IL-1β gene expression, contributing to inflammatory and neurogenic pain [44].…”
Section: Discussionmentioning
confidence: 99%